Identificación de especies arbóreas y arbustivas para la propuesta de un plan de manejo en zonas de alta vulnerabilidad física y ambiental en el sector San Pablo de la parroquia El Tingo – La Esperanza, cantón Pujilí, provincia de Cotopaxi en el periodo 2015 (transecto 5) - Lasluisa Guaña, Byron Patricio (2015)
This present work of investigation has permit to know the current state of the forest primary of La Esperanza, identification of tree species and shrub existing in the study area to the recommendation of afforestation and reforestation different agroforestry systems. It was in the study area (transect 5) of 1 ha, inventoried a total of 526 trees and shrubs representing a total of 31 families vegetables, for this reason the research topic. Identification of tree and shrub species for the proposed management plan in areas of high physical and environmental vulnerability in the San Pablo Parish of the Tingo - La Esperanza, Pujilí, raised Cotopaxi Province in the period 2015 ". Whose objectives were to, Identify native tree and shrub species transect 5, delimit the zones in the transect 5 of high physical and environmental vulnerability, Perform shrub socio-economic studies on the usefulness of tree and shrub species, Develop a proposed management plan in areas of high vulnerability and Environmental Physics, the most representative families: EUPHORBIACEAE (Rubber), followed the RUBIACEAE (Pambil), ROSACEAE family and family (Copal White), according to direct use value is 60% of species that are used for wood, plants medicinal and edible plants, and 40% for conservation and storage watersheds indirectly.